Edukasi Konsumsi Sayur dan Buah sebagai Upaya Peningkatan Kesehatan dan Pencegahan Penyakit pada Siswa SDS IT Al Wahdah Kendari - paridah; Fithria; Tyas Nur Fathona; Wa Ode Karmila; Sunarti; Devi Maharani; Ayuniar Firna; Erlina; Dewi Agustina; Naila Khalisa Sumadi; Diyna Awliya Aziyzah; Sudarni Sanipa; Fifi Indri Yanni; Sulistia Piadi; Dewa Hiro Prayatmi; Muh. Fahruly (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Vegetable and fruit consumption is an essential component of a healthy diet because it provides vitamins, minerals, dietary fiber, and antioxidant compounds that help maintain health and prevent various diseases. However, the intake of vegetables and fruits among school-aged children remains relatively low, highlighting the need for educational interventions to improve knowledge and awareness from an early age. This community service activity aimed to increase students’ understanding of the importance of consuming vegetables and fruits as natural sources of antioxidants. The activity was conducted on April 30, 2026, at SDS IT Al Wahdah Kendari and involved 25 students consisting of 14 girls and 11 boys. The educational methods included interactive lectures, discussions, question-and-answer sessions, and educational games supported by PowerPoint presentations. The materials covered the definition of antioxidants, the health benefits of vegetables and fruits, examples of antioxidant-rich foods, and the importance of daily vegetable and fruit consumption. Evaluation was carried out descriptively through observation of students’ participation and engagement during the activity. The results showed that students enthusiastically participated in all educational sessions, actively engaged in discussions, and were able to explain the benefits of vegetable and fruit consumption as well as identify various antioxidant-rich foods. This activity demonstrates that school-based nutrition education is an effective strategy for improving students’ understanding of healthy eating habits and promoting vegetable and fruit consumption from an early age.